EVALUASI BERBASIS GAME EDUKASI WORDWALL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMK NEGERI 1 KOTA PADANG - Misbar, Bilal Al; Putri, Amelia (Journal Intech and Education, 2025)
This study aims to evaluate the use of a Wordwall-based educational game to improve students' critical thinking skills at SMK Negeri 1 Padang City. The research problem is motivated by students' low critical thinking skills due to teacher-centered learning and the lack of use of interactive learning media. The research method used was a quasi-experimental pretest-posttest design. The subjects were 10th-grade students at SMK Negeri 1 Padang City, divided into an experimental class and a control class. The research instruments were a critical thinking ability test and a student response questionnaire. The results showed a significant increase in students' critical thinking skills after the implementation of the Wordwall educational game. Thus, Wordwall is an effective innovative learning medium for improving critical thinking skills in vocational high school students.